Síntese de nanolátex para aplicação como controlador de filtrado em cimentação de poços petrolíferos - Nascimento, Willian Barbosa Lima do (2021)
New additives applied to wells cementing have been developed in search of more and more efficient cement slurry systems for application in critical scenarios, especially those cases where the risk of gas migration is involved. The present work deals with the development of a new technology applied to the cementation of oil wells. Polystyrene dispersions were synthesized by a special emulsion polymerization process, enabling the production of small particle size dispersions (particle size smaller than 100 nm). These particles were characterized by gravimetry and dynamic light scattering analysis. Afterwards, these particles were blended with cement pastes and the paste was evaluated regarding consistency and static filtration tests. The cement paste additivated with 1.0 gpc (gallon per cubic foot of cement) of nanolatex showed consistency below 30 UC up to 190 °F. Values as small as 24mL/30min in fluid-loss were obtained and with plastic viscosity values within the standard for field application of the paste (208cP). These results showed that the use of nanolatex particles in cement paste represent a potential technology for application in oil wells with fluid-loss and gas migration risk.